Cymbopogon citratus industrial waste as a potential source of bioactive compounds. (12th December 2014) - Tavares, Filipa; Costa, Gustavo; Francisco, Vera; Liberal, Joana; Figueirinha, Artur; Lopes, Maria Celeste; Cruz, Maria Teresa; Batista, Maria Teresa
Abstract BACKGROUND Cymbopogon citratus (Cc), commonly known as lemongrass, is a very important crop worldwide, being grown in tropical countries. It is widely used in the food, pharmaceutical, cosmetic and perfumery industries for its essential oil. Cc aqueous extracts are also used in traditional medicine. They contain high levels of polyphenols, which are known for their antioxidant and anti‐inflammatory properties. Hydrodistillation of lemongrass essential oil produces an aqueous waste (CcHD) which is discarded. Therefore a comparative study between CcHD and Cc infusion (CcI) was performed to characterize its phytochemical profile and to research its antioxidant and anti‐inflammatory potential. RESULTS HPLC‐PDA/ESI‐MSn analysis showed that CcI and CcHD have similar phenolic profiles, with CcHD presenting a higher amount of polyphenols. Additionally, both CcI and CcHD showed antioxidant activity against DPPH (EC50 of 41.72 ± 0.05 and 42.29 ± 0.05 µg mL−1 respectively) and strong anti‐inflammatory properties, by reducing NO production and iNOS expression in macrophages and through their NO‐scavenging activity, in a dose‐dependent manner. Furthermore, no cytotoxicity was observed. CONCLUSION The data of this study encourage considering the aqueous solution from Cc leaf hydrodistillation as a source of bioactive compounds, which may add great industrial value to this crop. © 2014 Society of Chemical Industry